Analysis Of Employee Time Management Of The Vania Interior Furnishing Company Jakarta - Abiyyu Mufadhdhal Zhafran Ammar; Wiradendi Wolor, Christian; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research aims to analyze the time management of Vania Interior Furnishing Jakarta employees. Know the factors that cause poor time management at Vania Interior Furnishing Jakarta, and also know how to manage time well at Vania Interior Furnishing Jakarta. This research uses a qualitative method with a descriptive approach, namely by describing and analyzing the problems found. Data was collected by interviews, observation and documentation, with primary and secondary sources providing comprehensive insight. From the results of this research, it can be seen that the lack of poor time management is caused by employees still not understanding how to determine and sort out the priority scale of assigned tasks which results in a lack of work productivity. There are also obstacles that reinforce the influence and disruption of the environment in the workplace. causes reduced focus and results in poor time management applied by employees.